Pengaruh Model Pembelajaran Open Inquiry Terhadap Hasil Belajar Siswa pada Mata Pelajaran Fisika - Delianus Lembong; Muslimin (Jurnal Kreatif Online, 2021)
This study aims to determine whether there is an effect of the Open Inquiry learning model on student learning outcomes in physics. This type of research was a quasi-experimental research using the non-equivalent Pretest-posttest design. The population of this study were all students of class XI SMAN 1 Pasangkayu. The sampling technique used in this study was Purposive Sampling. The instrument to measure the learning physics was a validated multiple-choice test. The test of physics learning outcomes obtained showed that the average score of the experimental group was 15.16 higher than the control group, which was 10.56. Hypothesis test t-test (two parties), obtained tcount = 1.01 and ttable = 1.98 at the level of significance = 0.05. This means that the value of tcount is in the area of ​​rejection of Ho and acceptance of H1. So it can be concluded that there is an effect of the Open Inquiry learning model on student learning outcomes in physics subjects for class XI SMAN 1 Pasangkayu.